2014
DOI: 10.1371/journal.pgen.1004354
|View full text |Cite
|
Sign up to set email alerts
|

G×G×E for Lifespan in Drosophila: Mitochondrial, Nuclear, and Dietary Interactions that Modify Longevity

Abstract: Dietary restriction (DR) is the most consistent means of extending longevity in a wide range of organisms. A growing body of literature indicates that mitochondria play an important role in longevity extension by DR, but the impact of mitochondrial genotypes on the DR process have received little attention. Mitochondrial function requires proper integration of gene products from their own genomes (mtDNA) and the nuclear genome as well as the metabolic state of the cell, which is heavily influenced by diet. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
171
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(185 citation statements)
references
References 70 publications
13
171
1
Order By: Relevance
“…Indeed, our observations are in agreement with suggestions that germline removal promotes longevity in part by modulating insulin signaling and lipid metabolism (Hansen et al, 2013), and with expectations that naturally occurring variation in mitochondrial function and metabolism specifically affects male aging (Zeh and Zeh, 2005;Camus et al, 2012). Moreover, mitochondrialnuclear genetic interactions tied to aging are likely to include nuclear-encoded genes associated with reproduction-induced mortality (Tanaka et al, 1998;De Benedictis et al, 1999;Rand et al, 2006;Clancy, 2008;Zhu et al, 2014). A recent study found that interactions between genes spanning the mitochondrial and nuclear genomes were associated with components of male reproductive aging via direct effects on ejaculate weight and indirect effects on the size of eggs produced by females (Immonen et al, 2016).…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, our observations are in agreement with suggestions that germline removal promotes longevity in part by modulating insulin signaling and lipid metabolism (Hansen et al, 2013), and with expectations that naturally occurring variation in mitochondrial function and metabolism specifically affects male aging (Zeh and Zeh, 2005;Camus et al, 2012). Moreover, mitochondrialnuclear genetic interactions tied to aging are likely to include nuclear-encoded genes associated with reproduction-induced mortality (Tanaka et al, 1998;De Benedictis et al, 1999;Rand et al, 2006;Clancy, 2008;Zhu et al, 2014). A recent study found that interactions between genes spanning the mitochondrial and nuclear genomes were associated with components of male reproductive aging via direct effects on ejaculate weight and indirect effects on the size of eggs produced by females (Immonen et al, 2016).…”
Section: Discussionsupporting
confidence: 90%
“…Mice harboring Shox2 mutations (Cobb et al 2006), a complete deficiency of the HoxD cluster (Spitz et al 2001), and a Cre-dependent deletion of the entire HoxA cluster (Kmita et al 2005) were crossed, and the limbs of resultant progeny were analyzed for evidence of epistasis as newborns ( Figure 2). Intriguingly, while the removal of an individual Shox2 allele did not lead to limb shortening when the Hox genes were intact, this same mutation gave significantly truncated humeri when the HoxD cluster was disrupted (30% shorter than expected if HoxD genes did not affect the outcome of Shox2 mutation) [ Figure 2, A and A9: nonparallel lines in interaction plots are characteristic of interaction (e.g., Zhu et al 2014)]. Additionally, Prrx1-Cre; Shox2 fl/2 (or Shox2 c/2 ) animals, which have both copies of Shox2 removed from the limb mesenchyme, have disproportionately shorter ulnae when the HoxA genes are concomitantly disrupted (25% shorter than expected if…”
Section: Resultsmentioning
confidence: 99%
“…Lifespan studies in flies and worms are affected by diet and genetic background [162], so it is possible that ROS extends lifespan in certain conditions but not in others. Similarly, differences could be related to the nature of expression i.e.…”
Section: Is Where Ros Are Produced Important?mentioning
confidence: 99%